Developing an Index to Measure the Value of Health Care Provided to Stroke Patients - Halil Şengül; Sabahattin Aydın; Emrah Önder; Arzu Bulut (Annals of Indian Academy of Neurology)
Background and Objectives: It is possible to evaluate health services for stroke patients based on clinical benefits. However, in recent years, questions about responsiveness and outcomes have also emerged. Currently, there is no index that can assess health-care services for stroke patients along these three dimensions. This study introduces the first index designed to measure the value generated by health-care services for stroke patients. Methods: The Case-Mix Variables Data Collection Reference Guide, developed through a review of national and international stroke guidelines, underwent content validation by 10 neurologists and 10 interventional radiologists. Questions with a content validity index exceeding 0.80, along with the World Health Organization responsiveness questionnaire and the Patient-Reported Outcomes Measurement Information System Global-10 short form, were subjected to pairwise comparison by two neurologists, two interventional radiologists, and two public health physicians using the analytic hierarchy process (AHP) method. Results: In the comprehensive ranking of questions formulated using the AHP method and assessed by experts for importance and global weights, new stroke follow-up emerged as the most crucial, garnering an index score of 0.09. Conversely, questioning patients about their alcohol use status was deemed the least significant by experts, registering an index score of 0.00021. Conclusions: Our AHP analyses have furnished an index for gauging the factors that contribute to the value of health-care services rendered to stroke patients.